GENERAL PRINCIPLES OF PSYCHOLOGY (American Journal of Interdisciplinary Research and Development, 2024)
The subject of psychology and the history of its emergence Psychology, like other sciences, has followed a certain path in its development. At the end of the 19th century, at the beginning of the 20th century, the great psychologist G. Ebbinghaus said about psychology very briefly and precisely - psychology is a great pre-history and a very short history. The term "history" refers to the period when psychology was studied in honor of the separation from philosophy and closer to concrete sciences and the establishment of its own experimental method. It happened in the second half of the 19th century, but the sources of psychology disappear over the centuries. Four stages can be conditionally distinguished in its history. At each stage of the development of psychology, the subject of its study is filled with its own special content.